2021
DOI: 10.1021/acs.macromol.1c01490
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Synthetic Polypeptide–PolyHIPE Hydrogels with Stimuli-Responsive Behavior

Abstract: In this work, biodegradable macroporous stimuli-responsive polypeptide hydrogels based on L-glutamic acid (Glu) and its copolymers with equimolar amounts of L-phenylalanine (Phe) or L-lysine (Lys) were prepared by deprotection of the corresponding organogels under acidic conditions. The organogels were synthesized by ring-opening polymerization of Ncarboxyanhydride (NCA) derivatives of the corresponding α-amino acids in oil-in-oil high-internal phase emulsions (HIPEs) using the di-NCA derivative of L-cystine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…Recently, a high yield (B83%) of Cys 2 NCA via the two-step Fuchs-Farthing method was achieved using di-N-tert-butyloxycarbonyl-L-cystine (Boc-Cys 2 -OH) as the reactant, which was highly soluble in anhydrous ethyl acetate. 18,19 Since Boc-Cys 2 -OH is commercially available, the alternative Fuchs-Farthing strategy showed significant advantages compared with traditional methods.…”
Section: Synthesis Of L-cystine N-carboxyanhydridementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a high yield (B83%) of Cys 2 NCA via the two-step Fuchs-Farthing method was achieved using di-N-tert-butyloxycarbonyl-L-cystine (Boc-Cys 2 -OH) as the reactant, which was highly soluble in anhydrous ethyl acetate. 18,19 Since Boc-Cys 2 -OH is commercially available, the alternative Fuchs-Farthing strategy showed significant advantages compared with traditional methods.…”
Section: Synthesis Of L-cystine N-carboxyanhydridementioning
confidence: 99%
“…17 The addition of PLys and PGlu segments could make the core positively or negatively charged under physiological conditions, significantly enhancing the encapsulation of portable cargos. 19 For example, copolymerization with Glu increased the DLE of DOX up to 96% by simply mixing in an aqueous solution, avoiding the additional removal of organic solvents. 38 In another study, DOX and the hydrophobic drug resveratrol (RES) were loaded into the PGlu-containing nanogel separately.…”
Section: One-pot Polymerizationmentioning
confidence: 99%
“…3,4 Hydrogels are water-swollen three-dimensional viscoelastic macromolecular networks, crosslinked through either covalent bonds or non-covalent interactions such as electrostatic interactions, hydrogen bonding, hydrophobic association, and multivalent coordination. 5,6 Hydrogels have attracted extensive attention due to their versatility in composition, preparation, and resulting tunable properties such as swelling capacity, an interfacial affinity for target compounds, stimuli response, degradability, viscoelasticity, and network architecture. 7,8 Polymeric hydrogels have been used as functional materials in a variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Another class of polymers that are characterized by a suitable microenvironment for cell growth and can incorporate various functional groups into the structure is synthetic polypeptides prepared by ring-opening polymerization (ROP) of N -carboxyanhydrides (NCAs). , Synthetic polypeptide scaffolds are usually prepared in the form of microporous hydrogels, while macroporosity can be achieved by cryogelation , or porogen leaching . In our previous work, we have shown that polyHIPEs based on either synthetic polypeptides , or semicrystalline PCL can be prepared by ROP of NCAs or ε-caprolactone (CL), respectively, in the continuous phase of HIPE, resulting in two chemically and mechanically very different materials. However, due to the different reactivity of NCAs and lactone monomers as well as the nature of their propagating species, they cannot be readily copolymerized into corresponding poly­(ester-amides).…”
Section: Introductionmentioning
confidence: 99%